Technological innovation: Instructional communication media in History and Civic Education - Sujoko, Anang; Sobari, Wawan; Kurniawan, Tri Astoto; Domini, Fransiscus Xaverius; Wahyudi, Dicky; Huda, Mega Annisa Nuril (Universitas Padjadjaran, 2024)
Background: The teaching of history and civic education, intended to foster national identity, is not fully achieved due to the absence of technological innovation in the instructional communication media used in high schools. Purpose: This research explores the need for ICT among students and teachers as instructional communication media to promote national identity in history and civic education. Method: This research used the Research and Development (R&D) method. The initial design involved an exploratory qualitative approach, with data collected through interviews with teachers and students from four high schools in Malang City, along with documentation from the Kurikulum Merdeka. The data were then analyzed using interactive analysis techniques to understand the information technology and communication needs of students and teachers for simulating national identity in history and civic education. In the next stage, a development approach was carried out to construct a model for instructional communication media that incorporated technological innovation to simulate national identity in history and civic education. Results: The results indicate that instructional communication media for promoting national identity through simulated history and civics education require technological innovation in the form of the NUSANTARA.IN application, which offers. Teaching materials on history and civic education tailored to students’ characteristics, A virtual reality feature that provides students with a virtual learning experience in history and civic education, and User-generated content to build a network among students for learning history and civic education. Conclusion: NUSANTARA.IN, which includes three distinct features, is a technological innovation designed to serve as an instructional communication media, enabling students and teachers to simulate national identity in history and civic education. Implications: The findings from this study contribute to the theoretical advancement of instructional communication media by incorporating concepts such as virtual reality, user-generated content, and student networking in high school education.